The S-curve: Understanding the dynamics of worldwide financial liberalization - Nan Li; Chris Papageorgiou; Tong Xu; Tao Zha (Federal Reserve Bank of Atlanta, 2021)
Using a novel database of domestic financial reforms in 90 countries from 1973 to 2014, we document that global financial liberalization followed an S-curve path: reforms were slow and gradual in early periods, accelerated during the 1990s, and slowed down after 2000. We estimate a learning model that explains these dynamics. Policymakers updated their beliefs about the growth effects of financial reforms by learning from their own and other countries' experiences. Positive growth surprises in advanced economies helped accelerate belief updating worldwide, leading to the global wave of financial liberalization in the 1990s. The 2008 financial crisis, however, caused significant belief reversals.
Keywords: O11; O50; C11; C54; 330; financial reforms; informational diffusion; cross-country learning; belief updating; S-curve evolution; political costs; economic growth; financial crisis